Sleep promotes lasting changes in selective memory for emotional scenes - Payne, Jessica; Chambers, Alexis M.; Kensinger, Elizabeth A. (Frontiers in Integrative Neuroscience, 2012)
Although we know that emotional events enjoy a privileged status in our memories, we still have much to learn about how emotional memories are processed, stored, and how they change over time. Here we show a positive association between REM sleep and the selective consolidation of central, negative aspects of complex scenes. Moreover, we show that the placement of sleep is critical for this selective emotional memory benefit. When testing occurred 24hr post-encoding, subjects who slept soon after learning (24hr Sleep First group) had superior memory for emotional objects compared to subjects whose sleep was delayed for 16hr post-encoding following a full day of wakefulness (24hr Wake First group). However, this increase in memory for emotional objects corresponded with a decrease in memory for the neutral backgrounds on which these objects were placed. Furthermore, memory for emotional objects in the 24hr Sleep First group was comparable to performance after just a 12hr delay containing a night of sleep, suggesting that sleep soon after learning selectively stabilizes emotional memory. These results suggest that the sleeping brain preserves in long-term memory only what is emotionally salient and perhaps most adaptive to remember.